Cultural Education Based on Batik Introduction to Enhance the Creativity of Indonesian Children at the Al Ikhlas Art Studio in Sungai Penchala, Malaysia - Muhammad Saleh; Siroy Siroy; Nazib Baihaqi; M. Bachtiar Akbar Sitepu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Cultural education plays a vital role in fostering children’s creative thinking skills. Batik, as Indonesia’s cultural heritage, embodies artistic values, symbols, and life meanings that can be utilized as a medium of learning. This study aims to describe the implementation of batik-based cultural education in enhancing the creativity of Indonesian children at Sanggar Bimbingan Al Ikhlas Sungai Penchala, Malaysia. The research method employed is qualitative with a case study design. Data were collected through observation, interviews, and documentation. The findings reveal that batik activities improve children’s ability to generate ideas, select colors, and create patterns based on imagination. Moreover, children demonstrate increased confidence in expressing ideas through artwork. Teachers serve as facilitators who guide, motivate, and provide examples during the creative process. The conclusion indicates that batik-based cultural education enhances creativity, self-confidence, and cultural identity awareness among Indonesian children living abroad. This study contributes to the discourse on cultural education by highlighting batik as an effective medium for creative learning and identity development in diaspora contexts.